2011
DOI: 10.1136/jech.2010.108977
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing socioeconomic inequality in self-rated health in Tehran

Abstract: Sub-optimal SRH was more in lower than in higher economic status. After controlling for age, the levels of education and household wealth have the greatest contributions to SRH inequality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
58
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 37 publications
10
58
2
Order By: Relevance
“…Many of these studies revealed that higher socioeconomic status is correlated with the better health status (Kitagawa and Hauser 1973;Evans et al 1994;Wilkinson 1996;Gwatkin 2000;Wilkins and Marmot 2003;Deaton 2003). Conversely, similar research has shown that lower socio-economic status is correlated with poorer health status (e.g., Wagstaff 1991Wagstaff , 2002Deaton 2003;Hosseinpoor et al 2006;O'Donnell et al 2008;Nedjat et al 2012;). Studies of the older populations in both high and low income countries have pointed to the importance of income, education and racial or ethnic inequality (e.g., Schoenbaum and Waidmann 1997;Berkman and Gurland 1998;Deaton and Paxson 2001;Grundy and Sloggett 2002;Von dem Knesebeck et al 2003;Zimmer and Amorbsirisomboon 2001;Zimmer and Kwong 2003;Zimmer and House 2003;Zimmer and Kwong 2004;Huisman et al 2004;Matthews et al 2006;Sun and Liu 2006;Zhang 2008).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Many of these studies revealed that higher socioeconomic status is correlated with the better health status (Kitagawa and Hauser 1973;Evans et al 1994;Wilkinson 1996;Gwatkin 2000;Wilkins and Marmot 2003;Deaton 2003). Conversely, similar research has shown that lower socio-economic status is correlated with poorer health status (e.g., Wagstaff 1991Wagstaff , 2002Deaton 2003;Hosseinpoor et al 2006;O'Donnell et al 2008;Nedjat et al 2012;). Studies of the older populations in both high and low income countries have pointed to the importance of income, education and racial or ethnic inequality (e.g., Schoenbaum and Waidmann 1997;Berkman and Gurland 1998;Deaton and Paxson 2001;Grundy and Sloggett 2002;Von dem Knesebeck et al 2003;Zimmer and Amorbsirisomboon 2001;Zimmer and Kwong 2003;Zimmer and House 2003;Zimmer and Kwong 2004;Huisman et al 2004;Matthews et al 2006;Sun and Liu 2006;Zhang 2008).…”
Section: Introductionmentioning
confidence: 89%
“…In the last three decades, research on health inequalities has made tremendous progress in terms of quantifying socioeconomic inequalities and estimation of household or individual income and wealth based Concentration Index (CI) and its decomposition has emerged as a novel tool for health inequality assessment (Wagstaff 1991(Wagstaff , 2002Hosseinpoor et al 2006;O'Donnell et al 2008;Nedjat et al 2012;Arokiasamy et al 2012;Jain et al 2012;Nawal and Goli. 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have mainly focused either on inequality in the distribution of health workers or of health care resources (8,(11)(12)(13)(14)(15)(16). However, sound decisions are dependent on timely and accurate information concerning the distribution all needed health care resources.…”
Section: Introductionmentioning
confidence: 99%
“…According to this plan, the Government should make a strategic plan to reduce the number of poor individuals, and to decrease social and economic inequality. 5 Although access to prescription medicines is one of the greatest concerns of policy makers in Iran, 6,7 there is limited research on access to medicine in the country. Still, two arguments are frequently offered in national and international reports suggesting that access to medicines in Iran is generally acceptable 6,8 : the existence of a coherently implemented generic pricing system, and the active presence of local pharmaceutical producers.…”
Section: Introductionmentioning
confidence: 99%